2020
DOI: 10.21608/pserj.2020.25973.1038
|View full text |Cite
|
Sign up to set email alerts
|

Smart Breathing Walls for Integrated Ventilation: Heat Exchange and Indoor Air Quality Improvement

Abstract: There are many ideas and applications for incorporating nature into buildings to improve the quality of the indoor air and to achieve a higher percentage of natural ventilation with pollution reduction. One such idea is to use the Breathing Walls "BW" built on porous materials. The energy used in air-conditioned buildings is reduced by these materials. BW suggests a conceptual design suitable for hot climates and capable of controlling airflow across the entire surface and refrigerating internal spaces in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…An approach to consider is the implementation of porous walls or dynamic walls, which function to reduce interior humidity as part of an overall IAQ design strategy. These walls effectively prevent fungal growth on wall surfaces [3,26,27]. In addition to promoting excellent indoor air quality, especially in densely populated urban areas that suffer from air pollution.…”
Section: Indoor Air Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…An approach to consider is the implementation of porous walls or dynamic walls, which function to reduce interior humidity as part of an overall IAQ design strategy. These walls effectively prevent fungal growth on wall surfaces [3,26,27]. In addition to promoting excellent indoor air quality, especially in densely populated urban areas that suffer from air pollution.…”
Section: Indoor Air Qualitymentioning
confidence: 99%
“…In addition to promoting excellent indoor air quality, especially in densely populated urban areas that suffer from air pollution. It serves as both an effective insulator and an exceptional air filter, meeting ventilation requirements outlined by the ASHRAE standard [27,28]. According to the ASHRAE standard, various studies have demonstrated that it is necessary to replace more than half of a home's volume per hour with fresh air to maintain healthy indoor air quality.…”
Section: Indoor Air Qualitymentioning
confidence: 99%
“…Thermal comfort is concerned with the thermal environment formed from air temperature, airflow, air humidity, and solar radiation. Visual comfort is affected by the amount of light intensity in the room needed to move well [6]. The heat of sunlight can affect the temperature of space in three ways: conduction, convection, and radiation.…”
Section: Humidity Control Performancementioning
confidence: 99%
“…Furthermore, the potentiality of a good thermal performance of Tetra Pak when used as insulation material for the ceiling houses is high. d. Application of tetra pack coating on GRC walls Not only applied to the wall, the components in the tetra pack can also be applied as additional coatings on the walls or sheath components in the dominant building, so that the high humidity and solar radiation in humid tropical climates affect the performance of the walls that influence the comfort factor of occupants in the building [6]. So that with the coating or additional protection made from tetra pack can lower the room temperature during the day, thus making the walls more comfortable thermally.…”
Section: Figure 2 Ceiling Asymmetrymentioning
confidence: 99%